Oral Chinese herbal medicine in reducing the recurrence of colorectal adenoma after polypectomy: A protocol for the systematic review and meta-analysis. - Yi Cheng; Yuan Ming Di; Anthony Lin Zhang; Beiping Zhang; Charlie Changli Xue (PLoS ONE, 2023)
Background Colorectal adenoma (CRA) is a significant precancerous lesion of sporadic colorectal cancer (CRC). CRA is likely to recur after polypectomy, increasing the risk of CRC. Chinese herbal medicine (CHM) has been used to reduce CRA recurrence. This review aims to evaluate the effectiveness and safety of oral CHM in reducing CRA recurrence compared to other treatments (placebo, routine care, no treatment, and conventional medicine). Methods We will search for randomised controlled trials (RCTs) from nine major biomedical databases in English and Chinese from their inception to July 2023. The RCTs that investigate the effects of oral CHM in reducing CRA recurrence compared to other treatments will be involved. We will exclude trials using CHM extract or external application of CHM, cohort study and cross-section study. The Cochrane Risk of Bias Tool version 2 will be used to assess the quality of included studies. Data will be analysed using Review Manager software 5.4 and STATA. The random effect model will be used. The heterogeneity of intervention effects will be tested by Chi2 (Cochrane Q) and I2 statistics. Funnel plots will assess publication bias if more than ten studies are included. Subgroup and sensitivity analysis will be conducted when possible. Discussion This review will discuss the effectiveness and safety of oral CHM in reducing CRA recurrence. It will show the critical information for clinicians in the decision-making process and countries to develop clinical guidelines on CRA management. Systematic review registration PROSPERO CRD42023324197.